Using Biometric Technology in Rural Credit Markets : The Case of Malawi - Giné, Xavier (World Bank, Washington, DC, 2012)
The eleventh in series of impact notes profiles an innovative attempt to improve access to credit in Malawi through the use of biometric technology.